Anesthetic Effects of Clove Basil Essential Oil (Ocimum gratissimum) Microemulsion on Asian Redtail Catfish (Hemibagrus wyckioides) and Its Biochemical Stress Indicators - Lam, Phuong Hong; Vo, Huyen Da Nguyen; Truong, Linh My Thi; Dang, Dung My Thi; Dang, Chien Mau; Doan, Tin Chanh Duc; Mollaamin, Fatemeh; Monajjemi, Majid (MDPI AG, 2025)
Ocimum gratissimum (clove basil) essential oil is known for its anesthetic and stress-reducing effects in aquatic animals. In this study, it was synthesized into a microemulsion form and its anesthetic effects on Hemibagrus wyckioides (Asian redtail catfish) juveniles were evaluated. The clove basil essential oil was formulated into a stable oil-in-water microemulsion with a particle size of approximately 36.3 nm and a polydispersity index (PDI) of 0.17. The microemulsion, with concentrations ranging from 125 mg L−1 to 250 mg L−1, effectively induced sedation and anesthesia in fish. It took approximately 2 to 4 min for the fish to reach a state of sedation or anesthesia, depending on the concentration of the clove basil essential oil microemulsion used. After a 30 min induction period using clove basil essential oil microemulsion at concentrations of 125 mg L−1 and 175 mg L−1, the blood cortisol, glucose, and lactate levels, which are stress indicators in fish, were evaluated. The results indicated that the blood cortisol levels in the treatments (6.97 to 7.4 μg dL−1) were consistently lower than in the control group (17.17 μg dL−1) throughout the induction time. However, the glucose (5.6–6.75 mmol L−1) and lactate levels (3.23–5.41 mmol L−1) in the treatment groups increased acutely during the induction time but returned to normal levels (around 3.5 mmol L−1 and 1.6 mmol L−1, respectively) during recovery. This contrasted with the control group, where the lactate and glucose levels remained slightly elevated during the recovery period. Additionally, the recovery time in fish anesthetized with clove basil essential oil microemulsion was consistently short across all of the treatments. These findings highlight the potential application of clove basil essential oil, particularly in microemulsion form, as an effective anesthetic agent for fish.
Keywords: lactate; stress physiology; oil-in-water; QH301-705.5; Genetics; anesthesia; cortisol; glucose; Biology (General); QH426-470